2017
DOI: 10.1371/journal.pone.0170162
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Single-Chain Antibodies that Specifically Bind GI Noroviruses

Abstract: Norovirus infections commonly lead to outbreaks of acute gastroenteritis and spread quickly, resulting in many health and economic challenges prior to diagnosis. Rapid and reliable diagnostic tests are therefore essential to identify infections and to guide the appropriate clinical responses at the point-of-care. Existing tools, including RT-PCR and enzyme immunoassays, pose several limitations based on the significant time, equipment and expertise required to elicit results. Immunochromatographic assays avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…SPR biosensors are also used for virus detection. Phage antibodies were used as part of the SPR biosensor for the detection of norovirus [ 154 ], porcine circovirus [ 159 ], cowpea mosaic virus [ 213 ], SARS-CoV-2 [ 214 ], etc.…”
Section: Phage Antibodies For Virus Detection/identificationmentioning
confidence: 99%
“…SPR biosensors are also used for virus detection. Phage antibodies were used as part of the SPR biosensor for the detection of norovirus [ 154 ], porcine circovirus [ 159 ], cowpea mosaic virus [ 213 ], SARS-CoV-2 [ 214 ], etc.…”
Section: Phage Antibodies For Virus Detection/identificationmentioning
confidence: 99%
“…In addition, Holstein et al [17] also suggested that a recombinant antibody fragment could be used as a functional protein for a paper-based diagnostic test. ScFv is widely used for diagnostic purposes in many fields, and there are to detect diseases in humans or plants [33][34][35].…”
Section: Structural Bioinformatics Studymentioning
confidence: 99%
“…In particular, another study conducted by Kou et al [56] combining mAb NV23 and single-chain variable fragments (scFv) (HJT-R3-A9 antibody) for NoV capture and detection by a sandwich ELISA assay showed that all 25 NoV genotypes from stool samples could be identified with a Ct value of <31 and a limit of detection (LOD) of 1~10 ng/well for 8 GI and 13 GII genotypes, except 50 ng/well for GII.7 strains. In addition, Hurwitz et al [57] identified two scFvs (NJT-R3-A2 and NJT-R3-A3) that could detect NoV from infected clinical stool samples [57]. The LOD of NJT-R3-A2 scFv for the detection of GI.1 and GI.7 VLPs were 0.1 and 0.2 ng, respectively.…”
Section: Antibodymentioning
confidence: 99%
“…Shang et al [41] utilized SPR imaging to show that human milk glycan motif specifically binds to NoV and competitively inhibits viral capsid binding to host receptors. By SPR, Hurwitz et al [57] identified two scFvs (NJT-R3-A2 and NJT-R3-A3) that could bind to GI.1 and GI.7 VLPs, with Kd values of 27 nM and 49 nM, respectively. Similarly, Kim et al [137] demonstrated that concanavalin A (Con A) can bind with HuNoV (GII.4), with the metal coordination region of Con A identified as a major [129] with permission from the publisher).…”
Section: Surface Plasmon Resonance (Spr)mentioning
confidence: 99%